Copper(I) Acetate‐Catalyzed Cycloaddition between Azomethine Imines and Propiolates under Additive‐Free Conditions. Issue 28 (22nd August 2013) - Shao, Changwei; Zhang, Qun; Cheng, Guolin; Cheng, Chuanjie; Wang, Xinyan; Hu, Yuefei
Abstract: Because propiolates easily undergo base‐catalyzed self‐Michael addition, most popular catalytic systems in CuAAC cannot be used in the cycloaddition between azomethine imines and propiolates, because such reactions usually require the use of tertiary amines as additives (as base and/or ligand). We found that this problem can be resolved simply by using copper(I) acetate as catalyst, in which the acetate serves as a ligand and is converted into acetic acid during the reaction. Thus, copper(I) acetate catalyzed cycloaddition actually proceeds under additive‐free conditions (without exogenous ligand) to efficiently give 6, 7‐dihydropyrazolo[1, 2‐ a ]pyrazolone derivatives, in which the side‐reactions and byproducts caused by basic additives are completely avoided. Abstract : Copper(I) acetate proved to be a highly efficient catalyst for the cycloaddition between azomethine imines and propiolates under additive‐free conditions. As a result, base‐catalyzed self‐Michael addition of propiolates (side‐reaction) and the formation of associated byproducts caused by additives (serving as either base or ligand) is completely avoided.